Memristor-CNTFET based ternary logic gates. (February 2018) - Soliman, Nancy S.; Fouda, Mohammed E.; Radwan, Ahmed G.
Abstract: Multilevel electronic systems offer the reduction of implementation' complexity, power consumption, and area. Ternary system is a very promising system where more information is represented in the same number of digits compared to the binary systems. In this paper, ternary logic gates and some of their ternary circuit applications are presented using memristors and CNTFET inverter. This integration between memristors and CNTFET offers low static power, small area and high performance. The proposed circuits do not require refreshment like the previously published circuits and are not initial state dependent because the memristors switch between the low resistance and high resistance states according to each input. In addition, we investigate the mathematical analysis of the proposed memristor ternary logic gates circuits. In the circuit simulations, a VTEAM model is used to verify the proposed circuits. Finally, a comparison between the proposed circuits with the previously published implementations is discussed showing better performance in terms of power, delay and area.